Phosphorylation of Microtubule- Associated Protein 4 Promotes Hypoxic Endothelial Cell Migration and Proliferation - Junhui Zhang; Junhui Zhang; Lingfei Li; Lingfei Li; Qiong Zhang; Qiong Zhang; Xu Yang; Can Zhang; Xingyue Zhang; Xingyue Zhang; Dongxia Zhang; Dongxia Zhang; et al. (Frontiers Media S.A., 2019)
Endothelial cells play a critical role in the process of angiogenesis during skin wound healing. The migration and proliferation of endothelial cells are processes that are initiated by the hypoxic microenvironment in a wound, but the underlying mechanisms remain largely unknown. Here, we identified a novel role for microtubule-associated protein 4 (MAP4) in angiogenesis. We firstly demonstrated that MAP4 phosphorylation was induced in hypoxic endothelial cells; the increase in MAP4 phosphorylation enhanced the migration and proliferation of endothelial cells. We also found that hypoxia (2% O2) activated p38/mitogen-activated protein kinase (MAPK) signaling, and we identified p38/MAPK as an upstream regulator of MAP4 phosphorylation in endothelial cells. Moreover, we showed that the promigration and proproliferation effects of MAP4 phosphorylation were attributed to its role in microtubule dynamics. These results indicated that MAP4 phosphorylation induced by p38/MAPK signaling promotes angiogenesis by inducing the proliferation and migration of endothelial cells cultured under hypoxic conditions via microtubule dynamics regulation. These findings provide new insights into the potential mechanisms underlying the initiation of the migration and proliferation of endothelial cells.